Organizational Data - Stefan Liebig (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Organizational data describe central characteristics of organizations, their internal structures and processes as well as their behavior as corporate actors in different social and economic contexts. Firm and enterprise data are the most frequently used type of organizational data, but there is also a growing interest in data on schools, universities, and hospitals in the economic and social science research. In the last several years, there has been a substantial improvement in the accessibility and scientific usability of organizational data from official statistics. However, nonofficial organizational data produced within publicly funded research projects are practically impossible to obtain for secondary analyses. There is no documentation of the existing stock of non-official organizational data, and the methodological standards used for organizational research in Germany are low compared to the standards of international research. Against this background, it is recommended that efforts be focused on documenting and archiving the existing non-official organizational data for secondary analyses and on establishing higher methodological standards within this research field.
Keywords: 330; firms; organizations; methods of organizational research; micro data; secondary analysis